1987
DOI: 10.1111/j.1365-2125.1987.tb03078.x
|View full text |Cite
|
Sign up to set email alerts
|

Excretion of chloroquine and desethylchloroquine in human milk.

Abstract: The excretion of chloroquine and the major metabolite, desethylchloroquine, in breast milk was investigated in eleven lactating mothers following a single oral dose of chloroquine (600 mg base). The average milk to plasma concentration ratio at the 24th hour was 6.6 ± 2.4 for chloroquine and 1.5 ± 0.6 for desethylchloroquine in five of the volunteers. In five other volunteers the elimination half-life of chloroquine in milk was 8.8 ± 4.7 days which was longer than that in saliva (3.9 ± 1.0 days) from the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 7 publications
0
17
0
1
Order By: Relevance
“…In a number of studies, CQ or its metabolites (Edstein et al 1986;Ogunbona et al 1987;Ette et al 1987a, b, c;Akintonwa et al 1988) as well as HCQ have been shown to be excreted in breast milk (Nation et al 1984;Østensen et al 1985). Transplacental transmission of CQ and HCQ has also been observed (Akintonwa et al 1988;CostedoatChalumeau et al 2002).…”
Section: Excretion In Breast Milk and Transplacental Passagementioning
confidence: 89%
“…In a number of studies, CQ or its metabolites (Edstein et al 1986;Ogunbona et al 1987;Ette et al 1987a, b, c;Akintonwa et al 1988) as well as HCQ have been shown to be excreted in breast milk (Nation et al 1984;Østensen et al 1985). Transplacental transmission of CQ and HCQ has also been observed (Akintonwa et al 1988;CostedoatChalumeau et al 2002).…”
Section: Excretion In Breast Milk and Transplacental Passagementioning
confidence: 89%
“…The data quality is also variable because of small subject numbers in each study (1)(2)(3)(4)(5)(6)(7)(8)(9)(10), and wide variability in drug measurements per subject (13)(14)(15)(16)(17). Only three studies used AUC data to estimate milk Cavg.…”
Section: Discussionmentioning
confidence: 99%
“…Following the administration of a single chloroquine 300mg base dosage to lactating women, the milk: plasma ratio in AVCs ranged from approximately 2 to 4,f113] Following single oral doses of chloroquine 600mg, 24 hour milk: plasma concentration ratios approximated 7 for chloroquine and 2 for desethylchloroquine,f1l4] V sing peak milk concentrations and assuming a daily milk ingestion of lL by the infant, the maximum percentage of the maternal dose recovered in milk over 9 days was estimated at 0.7 to 4% of the matemalloading dose,f113. 114] During long term treatment, steady-state chloroquine concentrations may be higher and might expose the infant to higher drug concentrations. After a 5-day treatment totalling 2.1g of chloroquine to a lactating woman, the maximum amount of chloroquine ingested by the infant was estimated at 2 mg/day, which would be insufficient to induce any pharmacological effect.…”
Section: Clinical Pharmacokinetics In Pregnancy and Lactationmentioning
confidence: 99%